Органозберігаючі операції за раку щитоподібної залози: оцінка гормонального статусу у поопераційний період - Чернишов, С. В.; Шептуха, А. І.; Шляхтич, С. Л.; Бережна, І. Ю. (Clinical Endocrinology and Endocrine Surgery, 2014)
The analysis of the hormone-producing function of the thyroid tissue after conserving surgery for thyroid cancer was performed. After hemithyroidectomy postoperative hypothyroidism was developed in 25% of patients. Preoperative evaluation of TSH, ATPO, ATTG levels, and ultrasound characteristics can give a possibility to suppose how effective will work the remaining thyroid lobe. In case of high probability of postoperative hypothyroidism thyroidectomy should be recommended.